The Alternans before Cardioverter Defibrillator (ABCD) Trial - O’Loughlin, Taryn (MD Conference Express, 2006)
The Alternans Before Cardioverter Defibrillator [ABCD] Trial sought to determine if this noninvasive test could help predict the risk of sudden cardiac death and thereby direct the therapy of implanted cardiac defibrillators as good as, or better than current methods. Electrophysiology study is the prevailing method and involves threading a catheter through a patient’s veins into the heart to induce an arrhythmia with an electric shock. This invasive technique requires a high degree of skill, which limits its availability, and exposes the patient to a certain degree of procedural risk. The Microvolt T-Wave Alternans Test, however, involves only the topical placement of electrocardiogram sensors on the chest.